2019
DOI: 10.13044/j.sdewes.d7.0264
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach for Analysis of Higher Penetration of Variable Renewable Energy: Coupling of the Long-Term Energy Planning Tools and Power Transmission Network Models

Abstract: Many studies and scientific papers have been published that consider the integration of renewable sources in energy systems, using the least-cost optimization models as a long-term generation expansion planning tool. Supplementary to these analyses, this paper focuses on the transmission network capacity for acceptance of variable renewable energy. The hypothesis is that the simplified electric power transmissions system in the long-term planning modelling tools does not reflect properly the capacity for integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This paper presented a method that considered the reserve constraints incorporated in a DC OPF model on a 15-min time resolution. Moreover, the results of this study were obtained under demand uncertainty which is not considered in studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The proposed method filled in this research gap and the results demonstrated the necessity for more detailed modelling of the energy system.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…This paper presented a method that considered the reserve constraints incorporated in a DC OPF model on a 15-min time resolution. Moreover, the results of this study were obtained under demand uncertainty which is not considered in studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The proposed method filled in this research gap and the results demonstrated the necessity for more detailed modelling of the energy system.…”
Section: Introductionmentioning
confidence: 93%
“…This means that many studies that deal with energy systems would produce different results if the reserve constraints were not neglected (e.g. [7][8][9][10][11][12][13][14][15][16][17]). The ESS operated differently when RM was considered as part of its capacity was preserved in order to be able to offer cheaper up reserve.…”
Section: Figure 5 Marginal Energy Price Of the Observed System With A...mentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is adopted in transitioning the municipality of Aalborg to a 100% renewable smart energy system within Danish and European energy systems. Supplementary to the above analyses, Taseska-Gjorgievska et al ( 2019 ) focus on the transmission network capacity to accept variable renewable energy.…”
Section: Introductionmentioning
confidence: 99%